2020
DOI: 10.1111/1759-7714.13296
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clinicopathologic features on leptomeningeal metastasis from lung adenocarcinoma and treatment efficacy with epidermal growth factor receptor tyrosine kinase inhibitor

Abstract: Background: We investigated the risk factors for leptomeningeal carcinomatosis (LMC) and compared clinical efficacies of various treatment modalities including intrathecal (IT) chemotherapy in patients with lung adenocarcinoma harboring epidermal growth factor receptor (EGFR) mutations. Methods: Using clinical research data from the Asan Medical Center, we retrospectively analyzed data of patients diagnosed with LMC, confirmed via cerebrospinal fluid (CSF) analysis from January 2008 to December 2017. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
2
2
Order By: Relevance
“…It is reported that the incidence of LM from lung adenocarcinoma with EGFR mutation is higher than that from lung adenocarcinoma without EGFR mutation [7]. Kwon et al reported that most patients with LM already had other metastases, including brain, bone, and pleura [8]. The time of occurrence of postoperative LM was not clear in our patient, and in this rare case, LM was the initial and solitary site of postoperative metastasis.…”
Section: Discussioncontrasting
confidence: 53%
“…It is reported that the incidence of LM from lung adenocarcinoma with EGFR mutation is higher than that from lung adenocarcinoma without EGFR mutation [7]. Kwon et al reported that most patients with LM already had other metastases, including brain, bone, and pleura [8]. The time of occurrence of postoperative LM was not clear in our patient, and in this rare case, LM was the initial and solitary site of postoperative metastasis.…”
Section: Discussioncontrasting
confidence: 53%
“…This cohort study shows a relatively long median OS (8.0 months) in patients diagnosed with LM from NSCLC in a single institution, particularly in an EGFR-mutated group (12.6 months) versus previous published data ranging from 3 to 6 months [ 4 6 , 9 , 10 ]. The most important factor in NSCLC in recent years is an improved understanding of molecular characteristics that leads to precision therapy of metastatic NSCLC [ 18 ].…”
Section: Discussioncontrasting
confidence: 47%
“…There have been a few retrospective studies evaluating the prognosis of LM from NSCLC in the EGFR mutation subgroup. The median overall survival of these studies varies from 3 to 4 months [ 9 , 10 ] to 9–12 months [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, patients may present with one symptom or no symptoms at all, which means that a high index of suspicion should always be present [ 9 ]. Signs and symptoms are usually associated with meningeal irritation, cranial and spinal dysfunction, and/or increased intracranial pressure (Table 1 ) [ 1 , 10 - 14 ].…”
Section: Discussionmentioning
confidence: 99%